Technoligy venture blueprint company's name : AlQin Sdn Bhd / Noor Alia Yamin - Yamin, Noor Alia (2020)
AlQin Sdn Bhd is a start-up private company where the operation of the company is located at Ipoh, Perak and has been opened up to public on 13th Mei 2020. The business is owned and managed by one individual which known as a sole proprietorship or the sole trader. This type of business is unlimited liability which means that the owner carries the financial responsibility for all debts and losses suffered by the business. AlQin Sdn Bhd is a new company that produces innovation product that emphasize safety of occupants in house. Company’s mission is to improve the design and quality of current window grilles besides to provide high quality of product to the customer. Company aims to produce new product that have high technologies and to promote a profitable and sustainable business activity that meet demand of the customer